Komparasi Konsep El-Shadday dan Jubata Panange Sebagai Konstruksi Teologi Feminis Bagi Suku Dayak Kanayatn - David, Andre Vinsensius (Jurnal Teologi (Journal of Theology), 2024)
Women's struggles due to patriarchal domination do not only occur in the Bible. This has also been felt by women throughout the ages, including in the Kanayatn Dayak culture. The interpretation and implementation of the sacred texts of the Bible are dominated by men, so that the space for women to reflect on themselves as imago-dei and the image of God in women is very narrow. Not infrequently women who are already rooted in patriarchal culture consider this to be normal and without needing improvement. By historcal-critisizm approach for understanding concept of El-Shadday and Ethnography-Thick Description for the concept of Jubata Panange as God with a female face, which is read cross-textually as an effort to present feminist theology with a new nuance, namely the cultural context of Dayak Kanayatn. Abstrak Pergumulan perempuan akibat dominasi patriarki tidak hanya terjadi di dalam Alkitab. Hal ini juga dirasakan oleh perempuan sepanjang zaman, termasuk dalam budaya Dayak Kanayatn. Penafsiran dan implementasi teks suci Kitab Suci didominasi oleh laki-laki, sehingga ruang bagi perempuan untuk merefleksikan dirinya sebagai imago-dei dan citra Tuhan dalam diri perempuan sangat sempit. Tak jarang perempuan yang sudah mengakar dalam budaya patriarki menganggap hal tersebut sebagai hal yang wajar dan tanpa perlu perbaikan. Dengan pendekatan kritik-historis untuk memahami konsep El-Shadday dan Deskripsi Tebal Etnografi terhadap konsep Jubata Panange hadirlah sebuah gambaran mengenai Allah sebagai Tuhan berwajah perempuan, yang dibaca secara lintas tekstual sebagai upaya menghadirkan teologi feminis dengan nuansa baru, yaitu konteks budaya Dayak Kanayatn.